2022
DOI: 10.3390/cancers14040965
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Response Rate in Patients with Breast Cancer Brain Metastases after Systemic Therapy

Abstract: Brain metastases are detected in 5% of patients with breast cancer at diagnosis. The rate of brain metastases is higher in HER2-positive and triple-negative breast cancer patients (TNBC). In patients with metastatic breast cancer, the risk of brain metastases is much higher, with up to 50% of the patients having two aggressive biological breast cancer subtypes. The prognosis for such patients is poor. Until recently, little was known about the response to systemic therapy in brain metastases. The number of tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 87 publications
(95 reference statements)
0
1
0
Order By: Relevance
“…The PATRICIA phase II trial evaluated the combination of high-dose trastuzumab and pertuzumab in patients with CNS metastases who had progressed on prior radiotherapy. 27 , 28 , 29 The study reported a limited IC-ORR of 11% and a CBR of 51% at 6 months. 28 , 29 Another study, KAMILA, investigated the first ADC in metastatic BC, ado-trastuzumab emtansine (T-DM1).…”
Section: Discussionmentioning
confidence: 92%
“…The PATRICIA phase II trial evaluated the combination of high-dose trastuzumab and pertuzumab in patients with CNS metastases who had progressed on prior radiotherapy. 27 , 28 , 29 The study reported a limited IC-ORR of 11% and a CBR of 51% at 6 months. 28 , 29 Another study, KAMILA, investigated the first ADC in metastatic BC, ado-trastuzumab emtansine (T-DM1).…”
Section: Discussionmentioning
confidence: 92%